1997
DOI: 10.1183/09031936.97.10102327
|View full text |Cite
|
Sign up to set email alerts
|

Iron-binding proteins in sputum of chronic bronchitis patients with Haemophilus influenzae infections

Abstract: Airway inflammation during infection is associated with increased transudation of serum proteins and increased production of protein by the airway epithelium. We therefore, assessed whether Haemophilus influenzae infections in patients with chronic bronchitis are associated with increased levels of transferrin and lactoferrin in the sputum compared to uninfected patients.Sputum sol phase and serum samples from 14 infected and 13 uninfected patients with chronic bronchitis and from 12 bronchial asthma patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Previous authors have reported a lack of increase in respiratory lactoferrin levels with NTHI infection in COPD. 43 A clear explanation for this observation is lacking and needs further investigation. P Յ .001) (e- Fig 7).…”
Section: Effect Of Acquisition Of a New Bacterial Strain On Sputum Ammentioning
confidence: 98%
“…Previous authors have reported a lack of increase in respiratory lactoferrin levels with NTHI infection in COPD. 43 A clear explanation for this observation is lacking and needs further investigation. P Յ .001) (e- Fig 7).…”
Section: Effect Of Acquisition Of a New Bacterial Strain On Sputum Ammentioning
confidence: 98%
“…influenzae can also source iron through the uptake of host proteins such as LF, ferritin and haemoglobin (Pidcock et al, 1988;Vogel et al, 1997a). Significantly, studies have shown that TF levels are increased in the sputum of patients with chronic bronchitis associated with H. influenzae infections (Vogel et al, 1997b). However, whether the increased TF levels are the consequence of chronic bronchitis or are the cause of chronic infection and, therefore, the driver of disease, remains to be elucidated.…”
Section: Haemophilus Influenzae Streptococcus Pneumoniae Mycobactermentioning
confidence: 99%
“…Transferrin selectively accumulates in the lungs and is found primarily in the alveoli (3,29), where it appears to act as an important antioxidant in the protection of cellular membranes against iron-dependent lipid peroxidation (23). Notably, NTHI stimulates the production of transferrin, which is increased in the sputum sol phase of patients with chronic bronchitis who are infected with this bacterium (29). Thus, the ability of NTHI to gain access to the human iron pool by sequestering iron from transferrin may provide an important mechanism that enhances bacterial survival within the respiratory tract.…”
mentioning
confidence: 99%